A handbook of social science research. - Bouma, Gary D.; Atkinson, G. B. J.; Dixon, Beverly R. (Oxford : Oxford University Press, 1995)
What is social science research? How do you do it? What are the pitfalls? What are the tricks of the trade? This book provides answers to these and many other questions which need to be answered by students who seek to develop their research skills, and is an ideal introduction for those about to embark on research for the first time. Adopting a step-by-step approach, the authors clarify such issues as: how to isolate and define a problem; how to frame a hypothesis; how to choose and measure variables; how to choose a research design; how to select a sample. By asking students to grapple with fundamental questions, and by using case studies, they bring research theory and practice alive. The book is ideally suited to students taking courses in social science, social studies, or education. The new edition has been completely updated and includes a new chapter on qualitative research, as well as vital information on using computers in social science research.
1. How we know what we know and how we know we know -- 2. Research as a way of knowing -- 3. Selecting a problem -- 4. Selecting variables -- 5. Finding a variable's measurements -- 6. Selecting a research design -- 7. Selecting a sample -- 8. Collecting data -- 9. Summarizing and presenting data -- 10. Qualitative research -- 11. Drawing conclusions -- 12. Writing up your research -- Appendix A table of random numbers.
Previous ed.: published as Handbook of social science research / Beverly R. Dixon, Gary D. Bouma, G.B.J. Atkinson. 1987.
Includes index.
Includes bibliographical references and index.
Keywords: Social sciences -- Research